2002
DOI: 10.1111/j.1572-0241.2002.07030.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic colitis: clinical features, treatment, and outcomes

Abstract: Lymphocytic colitis typically presents in elderly patients as chronic diarrhea. Nocturnal stools, urgency, and abdominal pain occur frequently, as do weight loss, fecal incontinence, and concomitant autoimmune disorders. Many empiric treatment options are used, but overall response rates are disappointing. Randomized controlled trials are needed to determine the optimum therapeutic approach to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 13 publications
3
120
1
1
Order By: Relevance
“…Limitations of this study included limited information on over-the-counter medication usage, particularly nonsteroidal anti-inflammatory drugs (NSAIDs), which have been reported in 34-71% of patients with either LC or CC in published studies [18,[48][49][50]. Despite the lack of robust or consistent data, it is generally thought that NSAIDs probably play some role in the pathogenesis of MC, mostly based on case reports describing changes in diarrhea and histology with NSAID use and withdrawal [51].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Limitations of this study included limited information on over-the-counter medication usage, particularly nonsteroidal anti-inflammatory drugs (NSAIDs), which have been reported in 34-71% of patients with either LC or CC in published studies [18,[48][49][50]. Despite the lack of robust or consistent data, it is generally thought that NSAIDs probably play some role in the pathogenesis of MC, mostly based on case reports describing changes in diarrhea and histology with NSAID use and withdrawal [51].…”
Section: Discussionmentioning
confidence: 96%
“…This initially yielded 724 patients with a pathology report suggestive of MC during that period. Of these cases, 124 (approx 1 in every 5) were randomly selected for review by an expert GI pathologist (CH) to confirm the diagnosis of MC, based on previously published criteria for LC and CC [18][19][20][21]. We defined CC histologically to be the following: thickness of the collagenous subepithelial table [10 lm using an ocular micrometer, inflammation in the lamina propria consisting of mainly lymphocytes and plasma cells, lack of crypt architectural distortion, and regenerative-appearing changes in the surface and/or crypt epithelium.…”
Section: Inclusion Criteria For Microscopic Colitismentioning
confidence: 99%
“…There have been no prevalence studies of microscopic colitis reported from the Mayo Clinic. Pardi et al did report the clinical features in a cohort of 170 patients with biopsy-proven lymphocytic colitis, showing that 100% of these patients had diarrhea (23). However, the denominator (i.e., total number of patients with diarrhea undergoing biopsy) was not reported.…”
Section: Celiac Sprue Detectionmentioning
confidence: 93%
“…The peak incidence is around 65 years, but the age at onset can range between 10 and 90 years [4,6,7]. The peak onset for LC is comparable to that of CC, with similar age ranges, but here the female preponderance is less pronounced according to some studies [6,7,8,9]. …”
Section: Epidemiologymentioning
confidence: 96%